2007
DOI: 10.1167/iovs.06-0865
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Intracellular Phospholipases A2in the Human Eye: Involvement in Phagocytosis of Photoreceptor Outer Segments

Abstract: Various intracellular PLA(2) subtypes are present in the human retina. iPLA(2)-VIA may play an important role in the regulation of RPE phagocytosis of POS and may also be involved in the regulation of photoreceptor cell renewal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…Remaining to be defined are the regulatory events triggered by POS phagocytosis, including signals that activate phospholipase A 2 , to cleave docosahexaenoic chains from phospholipids of the POS disk membranes. Several phospholipases A 2 are present in the RPE cells, and recently a low molecular weight phospholipase A 2 was suggested to be engaged in POS phagocytosis (34). Another question is how the release of DHA is coupled to NPD1 synthesis through a 15-lipoxygenase enzyme (26).…”
Section: Discussionmentioning
confidence: 99%
“…Remaining to be defined are the regulatory events triggered by POS phagocytosis, including signals that activate phospholipase A 2 , to cleave docosahexaenoic chains from phospholipids of the POS disk membranes. Several phospholipases A 2 are present in the RPE cells, and recently a low molecular weight phospholipase A 2 was suggested to be engaged in POS phagocytosis (34). Another question is how the release of DHA is coupled to NPD1 synthesis through a 15-lipoxygenase enzyme (26).…”
Section: Discussionmentioning
confidence: 99%
“…Photoreceptors shed outer segment tips, which are then phagocytized by RPE cells in a daily, intermittent, and circadian fashion in mammals (19). The length of the outer segments remains constant as a consequence of the well-regulated biogenesis of outer segment membrane components in inner segments, coupled to the phagocytosis of the shed tips at an equal compensatory rate.…”
Section: Dha Supply and Retention In The Cnsmentioning
confidence: 99%
“…Experiments in which the isolated purifed subunits of Gt were added to Gt-poor ROS membranes in the presence or absence of light demonstrated that Gt ␤ ␥ subunits stimulate PLA2 activity ( 101 ). Furthermore, it has been recently reported that calcium-independent PLA2 group VIA may play an important role in the regulation of retinal pigment epithelium phagocytosis of photoreceptor OSs and that it may also be involved in the regulation of photoreceptor cell renewal ( 104 ).…”
Section: Plcmentioning
confidence: 99%